Developing Autonomy Through Student-Centered English Language Learning Process for Engineering Students - Olaya, Marian Lissett (GIST – Education and Learning Research Journal, 2018)
This article focuses on how the incorporation of autonomy into university students’ learning process improves their English language performance. The participants of this study were 25 students of engineering programs in a public university. Data collection was done through observation, a survey, and a group interview. Two categories that emerged after the data analysis supported the main finding that technology-based activities can be conceived as a starting point for the incorporation of autonomous learning in the English language education at the university.